Simulation Study of Gas Explosion Propagation Law in Coal Mining Face With Different Ventilation Modes - Liu, Jiajia; Zhang, Yang; Chen, Shouqi; Nie, Zishuo; Yang, Di (Frontiers in Energy Research, 2022)
In order to study the gas explosion shock wave propagation laws in coal mining faces with different ventilation methods, using Fluent simulation software, and combined with pipeline gas explosion experiments, and on the basis of building a three-dimensional mathematical and physical model, the gas explosion simulations under Y-type and W-type ventilation methods were carried out respectively. The results are described as follows: 1）The attenuation trend of overpressure peak value of inlet roadway 1# and working face with Y-type ventilation conforms to the power function form. Intake airway 2# and return airway have the same peak overpressure attenuation trend, but the peak value of overpressure in return airway is generally 10.6% higher than that in intake airway 2#, and its attenuation rate is a process from low to high and then to low.2）The peak attenuation trend of overpressure in intake airway 1# and 2# with W-type ventilation conforms to the form of power function, and the peak attenuation trend of overpressure in return airway conforms to the form of exponential function. The peak value of overpressure decreases with the increase of the distance from the explosion source, and its attenuation rate decreases gradually. The research results have important theoretical significance for improving the prevention of gas explosion in coal mining face with different ventilation modes.